Problem med röda hamburgare efter tillagning - Gossas, Carina (2007)
Persistent pink in beef patties and hamburgers is a problem in the meat industry that has been known for a few decades. It is a costly problem as it can give rejections of food by consumers. Studies around the world have tried to solve the problem but it still remains a mystery. There are many different theories of what is causing the red colour. Some of the most likly theories are reducing hemocromes, high microbiological loads, contamination of nitrite or organic/non organic substanses, DFD meat etc.